Applications of nanoparticles in the transdermal delivery of chemotherapy against breast cancer: a mini-review - Alwan, Laila A.; Abd Alhammid, Shaimaa Nazar (Pharmakeftiki, 2025)
Transdermal administration represents a promising drug delivery strategy due to its non-invasive nature and potential for controlled, sustained release. By circumventing hepatic first-pass metabolism, it may reduce the need for excessive dosing and enhance therapeutic efficacy. However, the transdermal delivery of chemotherapeutic agents for breast cancer remains challenging, primarily due to the poor skin permeability of most anticancer drugs, which typically exhibit high molecular weight and limited lipid solubility. This mini-review critically examines recent advances in nanoparticle-based systems designed to facilitate transdermal chemotherapy for breast cancer. We categorize the types of nanoparticles employed, discuss their mechanisms of action and therapeutic advantages, and outline future directions for research and clinical translation.